The Implementation Learning Media Based on a Culture to Develop Student Character - Sari, Dwhy Dinda; Ilham, Muhammad; Fuadi, Noval; Nurviani, Rahima (Journal of Islamic Education Students (JIES), 2024)
The research aims to find out how culture-based learning media to develop student character at Srikandi Kindergarten in Lhokseumawe City and what obstacles teachers find in the implementation in the classroom. This research uses a descriptive qualitative research approach. The subjects in the study were students at Srikandi Kindergarten Lhokseumawe City, class teachers and principals. Data analysis techniques in this study include data collection, data reduction, data presentation and conclusion drawing. The results of this study found that culture-based learning media significantly contribute to students' character development by encouraging a deeper awareness and appreciation of diverse cultural perspectives, beliefs and practices, culture-based learning media foster empathy and understanding of others by exposing children to the traditions, practices and ways of life of other cultures. Kindergarten children learn to recognize and respect human differences and similarities through stories, music and visual representations of different cultures. The barriers found were the students' different knowledge and viewpoints regarding culture.